2022
DOI: 10.3324/haematol.2022.280651
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated thrombotic thrombocytopenic purpura plasma induces calcium- and IgG-dependent endothelial activation: correlations with disease severity

Abstract: Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is characterized by a severe ADAMTS13 deficiency due to the presence of anti-ADAMTS13 autoantibodies, with subsequent accumulation of circulating ultra-large von Willebrand Factor (VWF) multimers. The role of endothelial cell activation as a trigger of the disease has been suggested in animal models but remains to be demonstrated in humans. We prospectively obtained plasma from the first plasma exchange of 25 patients during iTTP acute phase. iTTP but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Moreover, Ren et al showed that administration of xenogeneic AECA to rats led to dose-dependent and complement-mediated TMA features [110]. We also demonstrated a potential role of ADAMTS13 antibodies: anti-ADAMTS13 monoclonal antibodies purified from iTTP patients B cells induced an ECs activation calcium dependent leading to a degranulation of WPBs [68].…”
Section: What Are the Suspected Triggers For The Second Hit Hypothesis?supporting
confidence: 60%
See 2 more Smart Citations
“…Moreover, Ren et al showed that administration of xenogeneic AECA to rats led to dose-dependent and complement-mediated TMA features [110]. We also demonstrated a potential role of ADAMTS13 antibodies: anti-ADAMTS13 monoclonal antibodies purified from iTTP patients B cells induced an ECs activation calcium dependent leading to a degranulation of WPBs [68].…”
Section: What Are the Suspected Triggers For The Second Hit Hypothesis?supporting
confidence: 60%
“…We have recently shown high levels of plasmatic free heme in TTP patients. Furthermore, ECs treatment with hemopexin mildly decreased calcium influx and WPB degranulation in vitro, which supports a modest amplification role of free heme [68].…”
Section: Hemolysismentioning
confidence: 52%
See 1 more Smart Citation
“…In iTTP patients, circulating EC number and plasma biomarkers reflecting endothelial activation are increased and correlated with the outcome supporting a role of the endothelium in the pathophysiology of iTTP [ 24 ]. Recently, Tellier et al, reported that several plasmatic components, including anti-ADAMTS13 IgG, free heme and possibly others converge to induce EC activation ex vivo [ 25 ]. Interestingly the intensity of the ex vivo EC activation induced by iTTP patients' plasmas correlated with the disease severity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tellier et al, reported that several plasmatic components, including anti-ADAMTS13 IgG, free heme and possibly others converge to induce EC activation ex vivo [ 25 ]. Interestingly the intensity of the ex vivo EC activation induced by iTTP patients' plasmas correlated with the disease severity [ 25 ]. Among soluble factors released in iTTP, hemolysis-derived products (including cell-free heme, free-hemoglobin and bilirubin at high concentration [ 26 , 27 ]) are well known to be highly toxic for the endothelium [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%